NOVEL CHEMICAL METHODS FOR IDENTIFICATION AND DETERMINATION OF TRIPTANS IN PHARMACEUTICAL PREPARATIONS - Ahmed, Ahmed Othman (Journal of Medical Genetics and Clinical Biology, 2024)
Triptans referred as 5-HT1-receptor agonists are groups of medicines, that are utilized to treat migraine and certain other headaches. İn this study, zolmitriptan and Sumatriptan as a selective serotonin receptor agonist for the 1B and 1D subtypes have been studied. This study was conducted to investigate the qualitative determination of triptan drugs (sumatriptan and zolmitriptan) from their pharmaceutical preparation by using oxidation coupling reaction. We studied the interaction of drugs by using five different type of coupling reactions in the presence of potassium permanganate as an oxidizing agent. The final product was analysed under Uv-VIs spectrophotometer, and it was found that, the resultant product of zol-shc, zol-azo, zol-oxi, zol-chro and zol-blrch give maximum absorbance at 510 nm, 540 nm, 490 nm, 520 nm, 505 nm of wavelength repectively, compare to zolmitriptan at 240 nm. Similar results were observed for suma-shc, suma-azo, suma-oxi, suma-chro and suma-blrch 525 nm, 540nm, 515 nm, 530nm, 520 nm and 480 nm of wavelength respectively compared to pure sumatriptan of 280 nm. These methods provides an effective and less expensive method for measurement of the triptans specially for developing countries